FOOD AND NUTRITION EDUCATION ACTIVITIES AS A STRATEGY TO PROMOTE HEALTH IN EARLY CHILDHOOD EDUCATION: A LITERATURE REVIEW - Budelon de Macedo, Adriana (Health and Society, 2022)
OBJECTIVE: to search the scientific literature for articles on food and nutrition education activities as a strategy for promoting health in early childhood education. METHODOLOGY: This scientific article is a literature review. For the article to be written, the following databases were used: BVS Virtual Health Library, Academic Google, Lilacs and Scielo. Articles using the following indexes were included in the research: (nutrition education activities from 2010 to 2021). DATA SYNTHESIS: The articles collected for the research showed similar results: that nutrition education activities are important working tools for nutritionists and have positive long-term results in the health and eating habits of students. CONCLUSION: food and nutrition education activities are important to teach about eating in a playful way. And, keep these activities and interventions constant, to expose the children to constant learning about healthy eating and unhealthy eating.